Timing of routine infant vaccinations and risk of food allergy and eczema at one year of age. Issue 4 (8th February 2016) - Kiraly, N.; Koplin, J. J.; Crawford, N. W.; Bannister, S.; Flanagan, K. L.; Holt, P. G.; Gurrin, L. C.; Lowe, A. J.; Tang, M. L. K.; Wake, M.; Ponsonby, A.‐L.; Dharmage, S. C.; et al.
Abstract: Background: Epidemiological evidence suggests that routine vaccinations can have nontargeted effects on susceptibility to infections and allergic disease. Such effects may depend on age at vaccination, and a delay in pertussis vaccination has been linked to reduced risk of allergic disease. We aimed to test the hypothesis that delay in vaccines containing diphtheria–tetanus–acellular pertussis (DTaP) is associated with reduced risk of food allergy and other allergic diseases. Methods: HealthNuts is a population‐based cohort in Melbourne, Australia. Twelve‐month‐old infants were skin prick‐tested to common food allergens, and sensitized infants were offered oral food challenges to determine food allergy status. In this data linkage study, vaccination data for children in the HealthNuts cohort were obtained from the Australian Childhood Immunisation Register. Associations were examined between age at the first dose of DTaP and allergic disease. Results: Of 4433 children, 109 (2.5%) received the first dose of DTaP one month late (delayed DTaP). Overall, delayed DTaP was not associated with primary outcomes of food allergy (adjusted odds ratio (aOR) 0.77; 95% CI: 0.36–1.62, P = 0.49) or atopic sensitization (aOR: 0.66; 95% CI: 0.35–1.24, P = 0.19). Amongst secondary outcomes, delayed DTaP was associated with reduced eczema (aOR: 0.57; 95% CI: 0.34–0.97, P = 0.04) and reduced use of eczema medication (aOR: 0.45; 95% CI: 0.24–0.83, P = 0.01). Conclusions: There was no overall association between delayed DTaP and food allergy; however, children with delayed DTaP had less eczema and less use of eczema medication. Timing of routine infant immunizations may affect susceptibility to allergic disease.